Incorporating social innovations in the elaboration of disaster risk mitigation policies - Trejo-Rangel, Miguel Angel; Marchezini, Victor; Rodriguez, Daniel Andres; dos Santos, Daniel Messias; Gabos, Marina; de Paula, Aloísio Lélis [UNESP]; Santos, Eduardo; do Amaral, Fernando Sampaio (Elsevier, 2023)
Climate crisis requires intergenerational groups' participation to reduce their vulnerability and to promote disaster risk mitigation public policies. This paper analyzes what and how social innovations can nurture risk mitigation public policies to enhance flood resilience in small cities. A mixed-methods approach, which considered a survey with 231 participants (54% women, 45% men, and 1% non-identified) and the facilitation of a seminar with participatory methodologies, was implemented between August and October 2021, engaging municipal secretariats, civil defense, an NGO, schools, and residents of São Luiz do Paraitinga, Brazil. Most participants (205 out of 231 surveyed respondents) indicated that floods are the main hazards, and 90% stated that municipal authorities should lead prevention measures prioritizing ten social innovation actions to avoid and reduce the disaster risks. The survey's results were shared during a seminar that included serious gaming activities to identify, discuss and formulate implementation pathways (how, when, with whom, with what resources) for the prioritized social innovation actions. Among the measures are prevention and evacuation plans, which were significantly correlated (0.749), as well as natural areas restoration and conservation plans, risk areas tours, and children and youth engagement in disaster risk reduction.
Keywords: Capacities; Climate change adaptation; Flood resilience; Small cities